2022
DOI: 10.1108/rpj-08-2021-0219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of properties at the interface of deposited IN625 and mixture of IN625 SS304L by laser directed energy deposition and SS304L substrate

Abstract: Purpose Prior to manufacturing, designing plays a vital role in the selection of materials and other design parameters. Therefore, during the deposition of materials, substrate materials provide support and affect the microstructure of the deposits, which may not be desirable in the manufactured product. Hence, the main purpose of the study is to analyse the behaviour of the microstructure at the interface of deposited material and substrate. Design/methodology/approach In this study, two blocks of Inconel 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Few have used nickel superalloys and austenitic steel such as SS316 and IN718 [10,11], but only a few literature are found on IN625 and SS304L [12]. Besides FGM, very few works are reported in IN625 and SS304L [13][14][15]. Carroll et al [12] deposited a single block of IN625-SS304L FGM in which they characterised and did the chemical analysis using CALPHAD of the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Few have used nickel superalloys and austenitic steel such as SS316 and IN718 [10,11], but only a few literature are found on IN625 and SS304L [12]. Besides FGM, very few works are reported in IN625 and SS304L [13][14][15]. Carroll et al [12] deposited a single block of IN625-SS304L FGM in which they characterised and did the chemical analysis using CALPHAD of the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…However, the brush plating coating is shallow, the strength of the bond is low, there is a large residual stress generated, and the coating easily falls off [ 7 ]; the spraying process itself is low strength, not up to the strength of the metal itself, and the spraying layer will produce certain porosity, flow hanging, bubbles, unevenness and other problems [ 8 , 9 ]. However, laser cladding is a directional energy deposition (DED) technology [ 10 , 11 ], the principle of which is to use a high-energy density laser beam to metallurgically bond the powder to the substrate, with fast cooling and fast heating, which can improve the surface properties of the substrate material, making it stronger, have better wear resistance, higher thermal fatigue strength, etc. [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very few works are reported in the fabrication of functionally graded SS304L/IN625. [20][21][22][23] Carroll et al 20 developed an FGM block of a square crosssection of 16 mm wide and 34 mm tall by 910 W YAG laser using the DED technique. They conducted experimental and thermodynamic studies on FGM and found the presence of (Mo,Nb)C secondary phase which is responsible for crack development.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted experimental and thermodynamic studies on FGM and found the presence of (Mo,Nb)C secondary phase which is responsible for crack development. Tudu et al [21][22][23] deposited blocks of different mixture of IN625 and SS304L on SS304L substrate at laser power (P L ) of 1300 W and scanning speed (v) of 0.5 m/min using the LDED technique. They studied the influence of wire electro discharge machining (WEDM) on deposited blocks, 21 influence of substrate on different gradient 22 and material characterization of deposited blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation